2003
DOI: 10.1016/s0248-4900(03)00088-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taxol and okadaic acid on microtubule dynamics in thimerosal‐arrested primary mouse oocytes: a confocal study

Abstract: A pulse of thimerosal (TMS), a sulfhydryl reagent, induces an instantaneous, complete and long-lasting microtubule interphasic network disassembly in mouse primary oocytes, correlated with the irreversible inhibition of meiosis reinitiation This inhibition is bypassed by dithiothreitol (DTT) while thiosalicylic acid, an analog of TMS, does induce neither microtubules depolymerisation nor inhibition of reinitiation and resumption of meiosis. This strongly suggests that the dramatic and pleiotropic inhibitory ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The studies cited above identified a number of molecular targets for thimerosal, have including micronuclei induction, disturbances of intracellular calcium, and inhibition of glutathione content (Ueha-Ishibashi et al, 2005a;2004b;Westphal et al, 2003), but the unique dependence of the developing nervous system on growth factors suggests that the neurotrophins and their receptors represent a possible target for thimerosal. There are a several studies suggesting that thimerosal may alter neurotrophin signaling, including binding of secondary messengers (Vanlingen et al 2001), microtubule assembly (Alexandre et al 2003), and intracellular calcium concentrations (Ueha-Ishibashi et al 2004a). Neurotrophins, especially nerve growth factor (NGF), but also the related neurotrophins, brain-derived growth factor (BDNF), neurotrophin-3 (NT-3) and neurotrophin-4/5 (NT-4/5), are known to affect the biological behavior of neuronal cells during development, survival and differentiation of the central and peripheral nervous systems (Barde 1989;Thoenen 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The studies cited above identified a number of molecular targets for thimerosal, have including micronuclei induction, disturbances of intracellular calcium, and inhibition of glutathione content (Ueha-Ishibashi et al, 2005a;2004b;Westphal et al, 2003), but the unique dependence of the developing nervous system on growth factors suggests that the neurotrophins and their receptors represent a possible target for thimerosal. There are a several studies suggesting that thimerosal may alter neurotrophin signaling, including binding of secondary messengers (Vanlingen et al 2001), microtubule assembly (Alexandre et al 2003), and intracellular calcium concentrations (Ueha-Ishibashi et al 2004a). Neurotrophins, especially nerve growth factor (NGF), but also the related neurotrophins, brain-derived growth factor (BDNF), neurotrophin-3 (NT-3) and neurotrophin-4/5 (NT-4/5), are known to affect the biological behavior of neuronal cells during development, survival and differentiation of the central and peripheral nervous systems (Barde 1989;Thoenen 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Okadaic acid induced an approximate twofold increase in the frequency of catastrophic transitions and a threefold decrease in the frequency of rescue transitions (25). For mammalian oocytes, OA could induce the resumption of meiosis, including GVBD and mitosis promoting factor (MPF) activation, and metaphase spindle formation in mice (12,13,26). Taxol is known to promote microtubule assembly by shifting the equilibrium between tubulin dimer and polymer in favor of microtubular formation (14).…”
Section: Discussionmentioning
confidence: 78%
“…The synergistic effects of nicotine and OA or nicotine and taxol on oocyte maturation and chromatid separation is very complicated. Okadaic acid independently induces premature separation of sister chromatids while regulating oocyte maturation and the transition from metaphase to anaphase in the mouse (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations